Order in Chaos: Lesser-Conserved and Repeat Structures in Dehydrins - G. Richard Strimbeck (Biomolecules)
Dehydrins (Dhns) are a group of intrinsically disordered land plant proteins that are closely associated with tolerance of dehydrative stress. Dhns are recognized and classified by the presence and sequence of five different conserved segments, varying in length from 8 to 15 residues, separated by highly variable disordered regions. In addition to one or more copies of the diagnostic, fifteen-residue K segment, most Dhns can be classified into one of three major groups based on the mutually exclusive presence of three other conserved segments (H, Y, or F), with all three groups typically incorporating multi-serine S segments. Many Dhns also include repeat structures. From an input library of 8675 non-redundant candidate sequences, a specialized R script identified and classified 2658 complete and 236 partial Dhn sequences in all major green plant (Viridiplantae) lineages, including a few green algal genera. An examination of the connecting segments bridging the conserved segments identified additional conserved patterns, suggesting that multi-Y, S-K, and K-S domains may act as functional units. Dhn Decoder identified 857 Dhns with repeat structures, ranging from 3 short, simple repeats to elaborate variations with up to 45 repeats or repeats of up to 85 residues comprising 1 or more of the conserved segments, suggesting that internal sequence duplication is an important mode of evolution in Dhns.